Perilaku Pencarian Variasi: Ditinjau Dari Perspektif Psikologi Dan Imbasnya Pada Loyalitas Kesikapan Konsumen - Iin Mayasari (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2008)
This study examines the model that explains the internal aspect as the stimulusi in influencing consumers to do variety seeking. The conceptual model is discussed by applying the psychology perspective of the optimum stimulation level and the impact on attitudinal loyalty. The number of questionnaires is 1100 exemplars and distributed to seven universities in Yogyakarta. However, the appropriate questionnaires to be further analyzed are 654 exemplars. The hypotheses testing uses the structural equation modeling.